Toward a Resilient Banking Ecosystem: The Impact of Circular Economy and Green Finance on Bank Stability in ASEAN - Tara Diska Alodya Sari; Mohamad Adam; Muizzuddin (Proceedings of International Conference of Graduate School on Sustainability, 2026)
The ASEAN banking sector is crucial for regional growth but faces environmental and financial vulnerabilities. The Circular Economy (CE) and Green Finance (GF) are transformative paradigms to reconcile development with sustainability. However, a systematic synthesis of their collective impact on bank stability in ASEAN is absent. This study fills that gap. Employing a Systematic Literature Review (SLR) following PRISMA guidelines, we searched databases like Scopus and Web of Science (2014-2024). Using keywords including "circular economy," "green finance," and "bank stability," 358 articles were identified. After screening, 42 studies were selected for thematic synthesis. The analysis reveals three primary impact channels. First, CE and GF enable risk diversification by reducing exposure to carbon-intensive "brown" assets. Second, they enhance reputation, attract conscious investors, and ensure a stable funding base. Third, they foster improved risk management through rigorous due diligence. Challenges such as "greenwashing," a lack of standardization, and short-term costs were also identified. The synergistic application of CE and GF can be a cornerstone for a resilient ASEAN banking ecosystem. The benefits for long-term stability, however, are contingent on robust regulations, transparent reporting, and genuine integration into core strategies. Consequently, embracing sustainability is a strategic imperative for mitigating systemic risks and ensuring enduring stability.